Transcriptomic and metabolomic analyses reveal the spatial role of carnitine metabolism in the progression of hepatitis B virus cirrhosis to hepatocellular carcinoma - Gao, Pengxiang; Liu, Qiuping; Luo, Ziye; Pu, Wenjun (Frontiers in microbiology, 2024)
Liver cirrhosis (LC) and hepatocellular carcinoma (HCC) resulting from chronic hepatitis B virus (HBV) infection are major health concerns. Identifying critical biomarkers and molecular targets is needed for early diagnosis, prognosis, and therapy of these diseases. In this study, we explored the gene expression and metabolism in the liver tissues of LC, HCC, and healthy controls, to analyse and identify potential biomarkers of disease progression. Mass spectrometry imaging was used to evaluate the spatial distribution of key metabolites. The results revealed significant changes in gene expression and metabolic pathways along with disease progression. The upregulated genes were associated with extracellular matrix remodeling and cancer pathways, including LAMC1-3, COL9A2, COL1A1, MYL9, MYH11, and KAT2A. The downregulated genes were linked to immune response and fatty acid metabolism. Metabolomic analysis showed major changes in lipid and choline metabolism. Consistent changes in the expression of specific genes and metabolites were correlated with clinical data. Notably, metabolites such as L-acetylcarnitine, histamine, and 4-trimethylammoniobutanoic acid demonstrated high accuracy (AUC > 0.85) in distinguishing between healthy, LC, and HCC groups. This study identifies key gene and metabolite changes in HBV related LC and HCC, highlighting critical pathways involved in disease progression. Biomarkers like L-acetylcarnitine and KAT2A show promise for early diagnosis and prognosis, potentially improving outcomes for hepatitis liver disease patients.